Surprising nonreward and response effort: Extinction after progressive-ratio training in rats and pigeons - Conrad, Shannon E.; Guarino, Sara; Papini, Mauricio R. (Learning and motivation, 2020)
Rats and pigeons exhibit different extinction profiles after instrumental acquisition with large vs. small rewards. In rats, extinction is faster after large-reward training, but in pigeons, extinction is faster after small-reward training. Two experiments extended these findings to a progressive-ratio schedule with acquisition training with two reward magnitudes administered either between or within subjects. Both rats and pigeons, under both between- and within-subject conditions, exhibited higher breakpoints (the last completed ratio) when responding for 5 pellets per ratio vs. 1 pellet per ratio. However, between-subject training yielded faster extinction after training with 5 pellets than 1 pellet for rats, but the opposite trend for pigeons. Extinction effects were eliminated in within-subject training for rats, but remained unchanged for pigeons. These results are discussed in the context of frustration theory and the strengthening/weakening principle of learning.